|x - 1| + |2x - 3| =|3x - 4|
Answers
Answered by
0
Answer:
= 0
Step-by-step explanation:
(x-1) + (2x - 3)=(3x-4)
X - 1 + 2x - 3 = 3x - 4
3x - 4 = 3x - 4
3x - 3x - 4 +4=0
0=0
I hope helping you and following me
Answered by
5
Given equation is
Let first find the breaking points, by equating 0 to each Modulus term.
So, we get 3 breaking points.
So, 4 cases arises.
Case :- 1
We know,
So, given equation reduces to
which is always true.
Case :- 2
The given equation reduces to
Hence, there is no solution in this interval.
Case : - 3
The given equation reduces to
Hence, there is no solution in this interval.
Case :- 4
The given equation reduces to
which is always true.
So,
Solution of equation
is
Similar questions
Accountancy,
2 months ago
Math,
2 months ago
Math,
3 months ago
Math,
3 months ago
Physics,
11 months ago